2015
DOI: 10.1111/ijd.12850
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of patients with lower limb cellulitis and antibiotic usage in Hospital Kuala Lumpur: a 7‐year retrospective study

Abstract: Identifying clinical characteristics of those at risk may help to prevent recurrence of cellulitis and long-term complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In a similar study by Eid et al, closure was obtained at an overall average of 4.2 tightening sessions (range 3-7) whereas, Park et al and Cheng et al reported 2-6 sessions for wound approximation. [21][22][23] Marek et al and Chiverton et al suggested obtaining closure in single sitting. 20,24 We achieved wound approximation in 4 tightening sessions which was on par with other studies in literature.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study by Eid et al, closure was obtained at an overall average of 4.2 tightening sessions (range 3-7) whereas, Park et al and Cheng et al reported 2-6 sessions for wound approximation. [21][22][23] Marek et al and Chiverton et al suggested obtaining closure in single sitting. 20,24 We achieved wound approximation in 4 tightening sessions which was on par with other studies in literature.…”
Section: Discussionmentioning
confidence: 99%
“…The study population was similar to that described in literature with a predominance of older people and men. 3,11,12 The clinical presentations were also classical with diabetes mellitus as a major risk factor. 4,[13][14][15][16] Most of the patients received Inj crystalline penicillin and cloxacillin for Streptococci and Staphylococci.…”
Section: Discussionmentioning
confidence: 99%
“…3,11,12 The clinical presentations were also classical with diabetes mellitus as a major risk factor. 4,[13][14][15][16] Most of the patients received Inj crystalline penicillin and cloxacillin for Streptococci and Staphylococci. 13 Subcutaneous pressures were elevated in patients with cellulitis of the leg when compared to the normal leg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staphylococcus aureus and Streptococcus pyogenes are the organisms that cause staph infections the most frequently [4] . Venous insufficiency, lymphedema, and a previous episode of cellulitis are the most common risk factors for a return of cellulitis [5] . Infections can emerge everywhere there is a breach in the skin's protective barrier.…”
Section: Introductionmentioning
confidence: 99%